2012
DOI: 10.1007/s12031-012-9763-z
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Nonselective Cationic Channel Inhibitors Blunts the PACAP-Induced Increase in Guinea Pig Cardiac Neuron Excitability

Abstract: Calcium influx is required for the pituitary adenylyl cyclase activating polypeptide (PACAP)-induced increase in guinea pig cardiac neuron sexcitability, noted as a change from a phasic to multiple action potential firing pattern. Intracellular recordings indicated that pretreatment with the nonselective cationic channel inhibitors, 2-aminoethoxydiphenylborate (2-APB), 1-[β-[3-(4-methoxyphenyl)propoxy]-4-methoxy-phenethyl]-1H-imidazole HCl (SKF 96365), and flufenamic acid (FFA) reduced the 20-nM PACAP-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…We showed that a PACAP-induced calcium influx is a critical step in the peptide modulation of cardiac neuron excitability (50). Previously, calcium influx through a PACAP-enhanced, receptor-operated nonselective cationic channel was suggested (37). However, as described above, the present results indicate that a PACAP-enhanced inward current through a Ni 2ϩ -sensitive channel such as T-type or R-type calcium channels more likely contributes to the peptide-induced increase in excitability.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We showed that a PACAP-induced calcium influx is a critical step in the peptide modulation of cardiac neuron excitability (50). Previously, calcium influx through a PACAP-enhanced, receptor-operated nonselective cationic channel was suggested (37). However, as described above, the present results indicate that a PACAP-enhanced inward current through a Ni 2ϩ -sensitive channel such as T-type or R-type calcium channels more likely contributes to the peptide-induced increase in excitability.…”
Section: Discussionmentioning
confidence: 89%
“…Transcript levels were determined for the three different T-type calcium channel isoforms (Cav3.1, Cav3.2, and Cav3.3) from laser captured (PALM Microlaser Technologies, Thornwood, NY) cardiac ganglia (37). In brief, clusters of cardiac ganglion cells (ganglia) were identified on nine atrial cardiac ganglia whole mount preparations.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, FFA was proposed as a potentially effective agent for the treatment of epilepsy. FFA (30 μM) reduces the peptide-induced intra-cardiac neuron firing rate (Merriam et al ., 2012), which may involve the TRPC channel inhibition. A reduction of firing rate by FFA (20 μM) was also reported in GABAergic neurons, possibly through TRP current inhibition (Lee et al ., 2011b).…”
Section: Impact Of Ion Channels Modulation By Ffa On Physiologicalmentioning
confidence: 99%
“…In PC-12 cells, PACAP signaling also includes IP 3 production and TRP channel activation, but in this case the species implicated (i.e., TRPC1) is activated by depletion of calcium from the endoplasmic reticulum (35). Recently, TRPC channels have been suggested to underlie the excitatory effects of PACAP on cardiac neurons, excitation that was suppressed by SKF96365 (31). Further, corroborating an important role for TRPC channels in regulating CSN responses to PACAP, multiple TRPC channel proteins (TRPC1/3/4/5/6/7) are strongly expressed on glomus cells and/or the petrosal afferent nerve terminals that innervate them (5).…”
Section: Discussionmentioning
confidence: 99%